Assessment of the Plans to Optimize Antimicrobial Use in the Pediatric Population in Catalan Hospitals: The VINCat Pediatric PROA SHARP Survey - Borja Guarch-Ibáñez; Aurora Fernández-Polo; Sergi Hernández; Eneritz Velasco-Arnaiz; Montse Giménez; Pere Sala-Castellvi; Valentí Pineda; Susana Melendo; VINCat Pediatric PROA Group (MDPI AG, 2023)
In Spain, many programs have been introduced in recent years to optimize antimicrobial stewardship in pediatric care (known as pediatric PROA). However, information on the current situation of these programs is scarce. The present study assesses current antimicrobial use in pediatric care in the hospitals of Catalonia affiliated with the VINCat pediatric PROA group. Between December 2020 and January 2021, an electronic survey related to the design and use of PROA was administered to members of PROA teams in our hospital network. The survey was conducted at 26 hospitals. Twelve percent of the hospitals had pediatric PROA in operation, 42% were included in adult PROA, and 46% carried out pediatric PROA activities but not as part of an established program. At 81%, the pediatric PROA team included a pediatrician, in 58% a pharmacist, and in 54% a microbiologist. The main activities were monitoring the use of antimicrobials and bacterial resistance. Twenty-seven percent measured indicators regularly. The VINCat Pediatric PROA group's hospitals have implemented measures for optimizing antimicrobial stewardship, but few have a pediatric PROA program in place. Specific measures and indicators must be defined, and the resources available should be increased. The development of pediatric PROA should be monitored in the coming years.